High genetic variation and phylogeographic relations among Palearctic fairy shrimp populations reflect persistence in multiple southern refugia during Pleistocene ice ages and postglacial colonisation. (29th August 2019) - Lukić, Dunja; Waterkeyn, Aline; Rabet, Nicolas; Mioduchowska, Monika; Geudens, Bernard; Vanschoenwinkel, Bram; Brendonck, Luc; Pinceel, Tom
Abstract: Intense anthropogenic disturbance threatens temporary pond ecosystems and their associated fauna across the Palearctic. Since fairy shrimps (Crustacea, Branchiopoda) are endemic to temporary ponds, populations are declining due to habitat loss and it is important to define adequate units for conservation. Phylogeographic reconstructions, based on genetic variation, provide valuable information for defining evolutionary and conservation units, especially for organisms with high levels of cryptic diversity like many fairy shrimps. We studied a total of 152 individuals of the fairy shrimp Branchipus schaefferi from 79 populations across the Palearctic and used mitochondrial (CO1) and nuclear (ITS1) DNA data to reconstruct the phylogeography of the species. Our results show that B. schaefferi comprises four highly diverged (10.3–16.5%) evolutionary clades. The present‐day haplotypes within each of the clades probably diverged from lineages that were maintained in separate refugia during the Pleistocene ice ages. While two clades represent distinct geographic regions, the two remaining clades have more wide and overlapping ranges. In addition, the limited number of shared haplotypes among populations from geographically distant regions within three of the clades suggest recent long‐distance dispersal events. Overall, the studied B. schaefferi dataset comprises high levels of genetic differentiation, without a clear morphological signal. Phylogenetic searches and pairwise genetic distances suggest that the studied lineages belong to a complex of four morphologically cryptic species. Since these four evolutionary old clades persist (±2 million years), despite overlapping geographic ranges and since they span a variety of ecological conditions, they should be considered as separate evolutionary significant units for conservation.